Pengaruh Dimensi Talent Management Terhadap Kinerja Karyawan: Studi Empiris pada Perusahaan Internet Service Provider (ISP) PT XYZ - Desetyadi, Victor Hutomo; Sirait, Tongam (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The background of the research is based on the urgency of strategically managing talent to face the challenges of a dynamic and competitive digital industry. This study aims to analyze the impact of Talent Management dimensions on employee performance at the Internet Service Provider (ISP) company PT XYZ. The research method used is a quantitative approach with explanatory survey techniques. Data were collected through a Likert questionnaire from all active employees (n = 48), with 31 valid respondents. Multiple linear regression analysis was used to test simultaneous and partial effects. The research results show that Talent Management simultaneously does not significantly affect employee performance (p = 0.081). However, partially, two dimensions, namely Performance Management and Organizational Development, actually have a significant but negative effect. These findings indicate a mismatch in the implementation of programs that may lower employee perceptions of performance. Additionally, the dimension of Company Vision, Mission, and Guiding Principles shows a significant positive effect that is approaching significance (p = 0.051), indicating its strategic potential in influencing performance if further optimized. The success of Talent Management is greatly determined by the quality of implementation, employee perception, and the organizational context.